PENGARUH RANSUM DENGAN KADAR PROTEIN KASAR BERBEDA TERHADAP PERTUMBUHAN ITIK BETINA MOJOSARI - Muhammad Riswandha Imawan; Rudy Sutrisna; Tintin Kurtini (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
This study aims to determine the effect of diets with different crude protein levels on the growth of female ducks mojosari and determine the best treatment on the growth of female ducks mojosari study was conducted in September - November 2015 on cage in Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. Ducks used in this study were female ducks mojosari as many as 64 individuals. This study was conducted using a randomized block design (RBD) with four treatments and four groups. The treatments were given in this study with different levels of crude protein ration is R1: 16%, R2: 18%, R3: 20%, R4: 22%. The data obtained were analyzed using ANOVA using a 5% significance level. The parameters measured were feed intake, body weight and feed conversion. Based on these results that rations with different crude protein levels did not significantly (P>0,05) affect on feed intake, body weight and feed conversion ducks trial. Keywords: Ration, Crude Protein, Growth, Mojosari Female Ducks